Assessment of top management leadership and commitment to improve perishable food supply chain quality. (2018) - Siddh, Man Mohan; Soni, Gunjan; Jain, Rakesh
The analytic hierarchy process (AHP) is a technique for arranging and examining complicated judgements by the ample and realistic framework. This study was performed to attain the relative significance of the factors affecting the quality of top management leadership and commitment in perishable food supply chain. Three popular perishable food industries were acknowledged in a brainstorming phase and an expert group has been made and it consists of all stakeholders of perishable food supply chain. The input from the result was used for the pair wise comparison of the factors affecting quality of top management leadership and commitment to PFSCQ. The contrast of the alternatives in AHP is based on the input taken from an expert team involving of perishable food supply chain stakeholders who exist in each of perishable food industry under study.